Mesenchymal Stem Cells and Reticulated Platelets: New Horizons in Multiple Myeloma - Cristian Alejandro Mera Azaín; Johan Leandro Vargas Pasquel; Sandra Milena Quijano Gómez; Viviana Marcela Rodríguez-Pardo (Hematology Reports)
Multiple myeloma (MM) is a malignant plasma cell disorder characterized by the accumulation of abnormal plasma cells in the bone marrow. Mesenchymal stem cells (MSCs) and reticulated platelets (RPs) have been implicated in the pathogenesis of MM. This narrative review aims to explore the role of MSCs and RPs in the pathophysiology of MM, particularly their clinical use as possible variables of prognostic value in this hematologic neoplasia. The interaction between MSCs and MM cells within the bone marrow microenvironment supports MM cell survival, proliferation, and drug resistance. MSCs contribute to the development and maintenance of MM through the secretion of various factors, including cytokines, chemokines, and growth factors. Moreover, RPs, young and highly reactive platelets, have been implicated in promoting angiogenesis, tumor growth, and metastasis in MM. Several studies show that cells such as MSCs and platelets participate actively in the biology of the disease. Still, in clinical practice, they are not considered part of evaluating affected patients. In this review, we explore the possibility of including the evaluation of MSCs and PRs in the clinical practice for patients with MM as part of the strategies to improve the outcomes of this disease.